Sampled-data model predictive control using adaptive time-mesh refinement algorithms - Luís Tiago Paiva (2017)
We address sampleddata nonlinear Model Predictive Control (MPC) schemes, in particular we address methods to efficiently and accurately solve the underlying continuous-time optimal control problems (OCP). In nonlinear OCPs, the number of discretization points is a major factor affecting the computational time. Also, the location of these points is a major factor affecting the accuracy of the solutions. We propose the use of an algorithm that iteratively finds the adequate timemesh to satisfy some predefined error estimate on the obtained trajectories. The proposed adaptive timemesh refinement algorithm provides local mesh resolution considering a timedependent stopping criterion, enabling an higher accuracy in the initial parts of the receding horizon, which are more relevant to MPC. The results show the advantage of the proposed adaptive mesh strategy, which leads to results obtained approximately as fast as the ones given by a coarse equidistantspaced mesh and as accurate as the ones given by a fine equidistantspaced mesh. (c) Springer International Publishing Switzerland 2017.